2004
DOI: 10.1002/marc.200300307
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Polymorphism and Dual Crystalline Morphologies in Poly(hexamethylene terephthalate)

Abstract: Summary: The polymorphisms in poly(hexamethylene terephthalate) (PHT), along with their associated melting and spherulite morphologies, were examined by differential scanning calorimetry (DSC), wide‐angle X‐ray diffraction (WAXD), and polarized‐light microscopy (PLM). The morphology and crystal cells were dependent on the temperature of crystallization. When melt‐crystallized at low temperatures (90–135 °C), PHT showed at least five melting peaks and two re‐crystallization peaks upon DSC scanning, and the samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
43
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 24 publications
3
43
0
Order By: Relevance
“…In previous work, melt-crystallized PHT is already known to exhibit complex melting peaks with various states of polymorphism depending on T c . [28][29][30] Here, the objective in this study was to further clarify whether post-crystallization thermal annealing/scan-ning at temperatures higher than the original T c might induce polymorphism transition or lamellar thickening. Earlier work [28][29][30] has discussed and concluded that melting of P 1 leads to immediate re-packing into P 2 (or later P 3þ4 ).…”
Section: Effects Influencing Polymorphism In Phtmentioning
confidence: 99%
See 4 more Smart Citations
“…In previous work, melt-crystallized PHT is already known to exhibit complex melting peaks with various states of polymorphism depending on T c . [28][29][30] Here, the objective in this study was to further clarify whether post-crystallization thermal annealing/scan-ning at temperatures higher than the original T c might induce polymorphism transition or lamellar thickening. Earlier work [28][29][30] has discussed and concluded that melting of P 1 leads to immediate re-packing into P 2 (or later P 3þ4 ).…”
Section: Effects Influencing Polymorphism In Phtmentioning
confidence: 99%
“…[28][29][30] Here, the objective in this study was to further clarify whether post-crystallization thermal annealing/scan-ning at temperatures higher than the original T c might induce polymorphism transition or lamellar thickening. Earlier work [28][29][30] has discussed and concluded that melting of P 1 leads to immediate re-packing into P 2 (or later P 3þ4 ). Only a merged P 3þ4 peak is seen with melting/re-crystallization of P 3 at 140 C, whose total enthalpy of melting (48 J/g) does not change much in comparison to un-annealed PHT (DSC Trace-a).…”
Section: Effects Influencing Polymorphism In Phtmentioning
confidence: 99%
See 3 more Smart Citations